2014
DOI: 10.5194/sed-6-3419-2014
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adsorption, desorption and fractionation of As(V) on untreated and mussel shell-treated granitic material

Abstract: Abstract. As(V) adsorption and desorption were studied on granitic material, coarse and fine mussel shell, and granitic material amended with 12 and 24 t ha−1 fine shell, investigating the effect of different As(V) concentrations and different pH, as well as the fractions where the adsorbed As(V) was retained. As(V) adsorption was higher on fine than on coarse shell. Mussel shell amendment increased As(V) adsorption on granitic material. Adsorption data corresponding to the un-amended and shell-amended graniti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Osorio-López et al [ 12 ], Seco-Reigosa et al [ 16 ], and Rivas-Pérez et al [ 17 ] also showed increased As(V) sorption as a function of the As(V) concentration added for most of the soil and waste samples here used, although clearly lower As(V) concentrations (<1.3 mmol L −1 ) were added in these previous studies.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…Osorio-López et al [ 12 ], Seco-Reigosa et al [ 16 ], and Rivas-Pérez et al [ 17 ] also showed increased As(V) sorption as a function of the As(V) concentration added for most of the soil and waste samples here used, although clearly lower As(V) concentrations (<1.3 mmol L −1 ) were added in these previous studies.…”
Section: Resultsmentioning
confidence: 56%
“…In fact, many low-cost sorbents have been previously investigated regarding their As removal potential, some of them showing encouraging results [ 10 ]. We have previously studied As(V) retention on soils and wastes [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ], using low As(V) concentrations (<1.5 mmol L −1 ). In recent works, we used different sorbent materials to study As(V) and Cr(VI) competitive sorption [ 18 , 19 ], but non-competitive As(V) sorption/release was not investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, the utilization of complementary bio-sorbents would be interesting. Specifically, pine bark could be used to retain Cr(VI) [26,27], whereas mussel shell could be used to facilitate As(V) retention [28]. Some studies have also dealt with the retention of pollutants on wheat straw, although under conditions different from those of the present work.…”
Section: Implications Of the Researchmentioning
confidence: 99%
“…Ni 2+ showed notable sorption and an opposite trend to that of F − , with sorption percentage increasing when the highest Ni 2+ concentrations (3 and 6 mmol·L −1 ) were added. We have previously studied [10][11][12][13][25][26][27][28]] the effects of different concentrations, pH, incubation time, and other variables on As(V), Cr(VI), F − , and/or Ni 2+ retention on other sorbent materials, but it should be also performed for wheat straw in future works.…”
Section: Data Analysesmentioning
confidence: 99%
“…In fact, Fu and Wang [1] reviewed the sorption capacities of agricultural and industrial waste and by-products, as well as of various types of natural substances, finding promising results. In this regard, in the last years we have studied several sorbents for the removal or retention of cationic heavy metals (Cd, Cu, Hg, Ni, Pb, Zn) [16][17][18][19][20], and anionic pollutants (Cr(VI) and As(V)) [21][22][23][24][25][26][27][28]. However, as far as we know, no previous study has dealt with Cd and Pb retention on forest soil, vineyard soil, and pyritic material samples, as well as on fine mussel shell, oak ash, hemp waste and pine bark samples, differentiating between results corresponding to the individual materials and those corresponding to the soils and pyritic material amended with the by-products.…”
Section: Introductionmentioning
confidence: 99%